El De venustate dicendi de Fernando Manzanares y el Diálogo de la lengua de Juan de Valdés - Arcos Pereira, Trinidad (1997)
The purpose ofthispaper is twofold: to study the characteristics ofthe de uenustate dicendi, first book of the Flores rhetorici by F. Manzanares, and to analyse the relationship between the work ofthis late 15thcentury humanist and El diálogo de la lengua by Juan de Valdés, an author of the next generation.
Keywords: Manzanares, F; Valdés, Juan de, -- ca. 1509-1542